In Search of Spirit Dimension of Europe: „Espaces” Project and Figure of Edith Stein, Co-Patroness of the Europe - Grubka, Marek (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
Reflection upon u the contemporary shape of the European Union inevitably leads to the analysis of the state of the soul of Europe, its internal dynamism. Similar questions were posed by Edith Stein, a philosopher, Carmelite and martyr of Auschwitz in the period after World War I, as well as before and after the onset of World War II. From a different perspective, in another time and another space, an European Association ‘Espaces’, which was established in1990, carried out analysis and reflection on the state of the soul of Europe, its challenges and future. The initiative originated in cooperation with the European Commission chairman Jacques Delors and lasted over twenty years. What connects the figure of Edith Stein, as the patron of Europe and the Dominican initiative Espaces? In short, care about the shape of Europe, particularly of its spiritual heritage.